Genomic analysis of matrix metalloproteinases affecting the prognosis and immunogenic profile of gastric cancer - Yuan, Chaofeng; Yuan, Jialin; Xiao, Huijie; Li, Haitao; Jiang, Yang; Zhai, Rongnan; Zhai, Jinjing; Xing, Hua; Huang, Jiannan (Frontiers in Genetics, 2023)
This study systematically and comprehensively analyzed the characteristics of matrix metalloproteinases (MMPs) in gastric cancer (GC) and revealed the relationship between MMPs and prognoses, clinicopathological features, tumor microenvironment, gene mutations, and drug therapy response in patients with GC. Based on the mRNA expression profiles of 45 MMP-related genes in GC, we established a model that classified GC patients into three groups based on cluster analysis of the mRNA expression profiles. The 3 groups of GC patients showed significantly different prognoses as well as tumor microenvironmental characteristics. Next, we used Boruta's algorithm and PCA method to establish an MMP scoring system, and found that lower MMP scores were associated with better prognoses, lower clinical stages, better immune cell infiltration, lower degrees of immune dysfunction and rejection, and more genetic mutations. whereas a high MMP score was the opposite. These observations were further validated with data from other datasets, showing the robustness of our MMP scoring system.Overall, MMP could be involved in the tumor microenvironment(TME), clinical features and prognosis of GC. An in-depth study of MMP patterns can better understand the indispensable role of MMP in the development of GC and reasonably assess the survival prognosis，clinicopathological features and drug efficacy of different patients, thus providing clinicians with a broader vision of GC progression and treatment.